Whole Genome Sequencing of Danish Staphylococcus argenteus Reveals a Genetically Diverse Collection with Clear Separation from Staphylococcus aureus - Hansen, Thomas A.; Bartels, Mette D.; Høgh, Silje V.; Dons, Lone E.; Pedersen, Michael; Jensen, Thøger G.; Kemp, Michael; Skov, Marianne N.; Gumpert, Heidi; Worning, Peder; Westh, Henrik (Frontiers in Microbiology, 2017)
Staphylococcus argenteus (S. argenteus) is a newly identified Staphylococcus species that has been misidentified as Staphylococcus aureus (S. aureus) and is clinically relevant. We identified 25 S. argenteus genomes in our collection of whole genome sequenced S. aureus. These genomes were compared to publicly available genomes and a phylogeny revealed seven clusters corresponding to seven clonal complexes. The genome of S. argenteus was found to be different from the genome of S. aureus and a core genome analysis showed that approximately 33% of the total gene pool was shared between the two species, at 90% homology level. An assessment of mobile elements shows flow of SCCmec cassettes, plasmids, phages and pathogenicity islands, between S. argenteus and S. aureus. This dataset emphasizes that S. argenteus and S. aureus are two separate species that share genetic material.